Diversity of Actinomycetes Isolated from Peat Soil of Undistrubed Forest and Pineapple Plantation in Sessang, Sarawak - Heng, Jeffrey Lim Seng; Hamzah, Halizah; Nejis, Norzaimawati Aman (Journal of Tropical Biodiversity and Biotechnology, 2024)
Peatland plays an important role not just as a carbon store but also in facilitating the flux of greenhouse gasses into the atmosphere. Apart from that, peatland is also home to a diverse population of microorganisms such as bacteria, fungi, and actinomycetes. Actinomycetes were known to be one of the most ubiquitous microbes that can be found in most of the soil types including peat soil. In this study, seventy isolates of actinomycetes were isolated from the peat soil using the soil dilution method. The 70 isolates of actinomycetes were later screened for their ability to produce secondary metabolites and antimicrobial activities using the agar diffusion method before the selected potential isolates were identified by targeting their 16S rRNA region. The results obtained showed 34.3% produce cellulase followed by, 12.8, 31.7, 80.0, and 51.4% for mannanase, xylanase, lipase, and protease respectively. The percentage of actinomycetes producing antimicrobial activity was 27.1 and 21.4% for Ralstonia solanacearum and Colletotrichum gleosporioides respectively. All the selected isolates of actinomycetes were identified as belonging to the genus of Streptomycetes spp. The potential actinomycetes were stored in freeze-dried form for future usage. This study showed that  more diverse population of actinomycetes was obtained from the undisturbed forested peat soil area ecosystem compared to the agricultural peat soil area.